O historiador como inquisidor ou como antropólogo?: Um questionamento para os "historiadores orais" - Gallian, Dante Marcello Claramonte (Revista de História, 1992)
To call the atlention of the historians who work with documents of dialogue structure, especially those derived of the technique of Oral History, to the episthemological and methodological problems of the New Anthropology is the main objective of this article. Starting from the analogy which historian Carlo Ginzburg proposes between the anthropologist and the inquirer, the purpose is to put back into discussion the problem of the relationship between the researcher and the narrator in the process of creating and interpreting oral sources.